Mutual Coupling Reduction Using Improved Dual-Layer Mushroom and E-Shaped Stub - Chunxia Cheng; Liyan Luo (International Journal of Antennas and Propagation)
The improved dual-layer mushroom (IDLM) and back-to-back E-shaped stubs for mutual coupling reduction between microstrip patch antennas are presented in this paper. The IDLM unit consists of one upper layer complementary split-ring resonator lattice and four lower layer lattices, whose centers are connected to the ground by a pin. The decoupling structure can prevent the surface current from one antenna port to another, so as to improve the isolation between the antennas. The proposed antenna works in the open wireless communication band of 2.45 GHz. Using the proposed decoupling structure, a low mutual coupling level ranging from −27 to −40 dB is obtained when the center distance of the adjacent patches is 0.5λ0. The total size of the decoupling antenna is 99 × 41 × 2.4 mm3 with a frequency range of 2.42–2.48 GHz for S11 < −10 dB. The proposed decoupling structure can also improve the average gain and efficiency of the antenna by 0.1 dB and 5%, respectively. The antenna is studied from the aspects of isolation, return loss, current and electric field distribution, radiation pattern, and diversity performance. The designed decoupling antenna is fabricated and measured. The pattern, isolation, and return loss of the tested results show good consistence with the simulation results. The diversity gain and envelop correlation coefficient of the diversity performance show that the designed antenna can be used in MIMO or Rx/Tx systems.